Fingerprints of relaxor ferroelectrics: Characteristic hierarchical domain configurations and quantitative performances. (December 2020) - Bian, Jihong; Xue, Pan; Zhu, Ren; Wang, Lei; Yang, Bian; Li, Tao; Hu, Qingyuan; Shen, Lvkang; Wang, Jianwei; Lu, Guanghao; Yang, Yaodong
Highlights: Relation between domains and in-situ quantitative intrinsic properties is revealed. Domain configurations of PMN-PT single crystals show strong composition dependence. Polygonal lamellar domains in the MPB composition own better performances. The original local d33 of polygonal domains is 14 pm V −1 . Polygonal domains have low coercive voltage and high effective Young's modulus. Abstract: Ferroelectrics' structure-property relationships are of guiding significance in high-performance material designing and usually clarified from the aspect of symmetries, which is arduous and costly. On the principle of convenience, here, the concept that domains can provide a brandnew nondestructive and fast way for this relationship clarification is demonstrated. Utilizing scanning probe microscopy, quantitative original local elastic/piezoelectric/ferroelectric performances of various characteristic domain configurations are directly investigated in relaxor ferroelectric Pb(Mg1/3 Nb2/3 )O3 -PbTiO3 single crystals. Among them, the polygonal lamellar domains with coexistence of straight c, a and c/a walls in the at-morphotropic phase boundary composition, own high surface effective Young's modulus (average values close to 160 GPa), strong original average local piezoresponse (8.5 pm) and effective longitudinal piezoelectric response (d33, 14 pm V −1 ), together with ease of electrical switching. Low free energy barrier and strong piezoelectric anisotropy contribute intrinsically to these better functionalities. Higher and easier domain wall motion, larger ratio of c + /c − domains, and larger depolarization and elastic energies stemmed from larger domain width/size act as extrinsic factors. These results help to understand relaxor ferroelectrics comprehensively and provide a reference of domain-based structure selection for better material design. Graphical abstract: Relationships between various characteristic vertical and lateral domain configurations and their original quantitative local performances in PMN-x%PT single crystals are clarified by SPM. Polygonal lamaller domains with various wall kinds own the highest original elastic/piezoelectric/dielectric properties. More c +, larger domain width and higher domain wall motion contribute extrinsically to these functionalities. Image, graphical abstract